(untitled) (Damascus University Journal of educational and Psychologyical sciences, 2024)
The research aims at a comparative study of healthy behavior between a sample of students from the Al-Fourat and Damascus Universities, and then to know the role of the health education textbook in developing positive health behaviors on a sample of students from Al-Fourat University, and to know the differences between the study samples in terms of the variables of "acadimic year, age, gender, marital stuatus and financial status". . The sample consisted of (232) male and female students distributed according to the variables studied, and after testing the hypotheses, the results showed that the students of the two universities differed in terms of the measure of healthy behavior and statistical significance. The results also showed that there were no statistically significant differences when studying the variation between the university variable and the studied variables except for the material status variable, and all students had a positive attitude towards healthy behavior. As for the measure of the scientific content of the book, the differences were statistically significant for all the studied variables except for the material status variable.